ANALISIS PREDIKSI KELULUSAN UJIAN LABOR PROFESIONAL MAHASISWA UNIVERSITAS METAMEDIA - Karfindo Karfindo; Rifa Turaina; Rusli Saputra (Ensiklopedia of Journal, 2023)
Increasing developments in the field of Artificial Intelligence (AI) have made many other fields begin to apply AI in data analysis in their respective fields, such as health, finance, education, and others. In the field of education, it is currently known as Ecuation Data Mining (EDM) which is a scientific discipline for exploring data originating from educational contexts. At metamedia university there are already many information systems used to process student data. With this data warehouse, the authors try to perform data analysis using the CRIPS-DM method. CRIPS-DM is an industry independent process model for data mining. One of the problems that occurs is failure in the professional labor exam. The author tries to apply the naïve Bayes machine learning algorithm to analyze the causes of student failure. The data that is processed is data on the value of labor exams, data on the value of 6 courses. To evaluate the accuracy of the writer using a confusion matrix with an accuracy rate of 68.75%.